Psychosocial Factors Influencing Outdoor Recreation During the COVID-19 Pandemic - Mateer, Timothy J.; Rice, William L.; Taff, Brendan Derrick; Lawhon, Ben; Reigner, Nathan; Newman, Peter (Frontiers in Sustainable Cities, 2021)
The COVID-19 pandemic has created an unprecedented disruption to daily life for large swaths of individuals and resulted in potentially widespread implications for individuals’ health and wellbeing. This study utilized an online survey of avid outdoor recreationists to understand the psychosocial factors influencing recreationist behaviors during the COVID-19 pandemic across rural, urban cluster, and urban communities in the United States. Confirmatory factor analyses indicate that the five studied psychosocial factors - perceived risk, social norms, recommendations from authority, health benefits, and lifestyle adjustments - exist as unique constructs influencing individuals’ outdoor recreation behaviors. Repeated measures analyses suggest individuals rated seeking benefits to their general health as most important when making outdoor recreation decisions, followed by recommendations from authority, then perceptions of risk, with lifestyle adjustments and social norms rated as least important. Lastly, analysis across community types indicated individuals across the rural-urban gradient weighed perceptions of risk and recommendations from authority differently when making outdoor recreation decisions. Managerial implications and future directions for research are discussed.